Workshop on Requirements, Use Cases, and User Studies in Digital Music Libraries and Archives (RUCUS) 2019: A Half-Day Workshop - Weigl, David M. (2019 ACM/IEEE Joint Conference on Digital Libraries (JCDL), 2019)
Music has widespread appeal as a subject for research, drawing on diverse perspectives from a large variety of academic fields. Digital libraries, serving as centres for interdisciplinary exchange, enable collaborative interactions with multimodal music resources between users and across use contexts. A thorough understanding of such interactions on a human level, incorporating concerns around user expectations, requirements, and information behaviours is critical in order to evaluate and inform the development of information systems to fulfil this purpose. The proposed half-day workshop on Requirements, Use Cases, and User Studies in Digital Music Libraries and Archives (RUCUS) provides a concerted platform for intellectual exchange between scholars, practitioners, and system developers concerned with user-centric issues of music information research, a topic of primary concern for the development and understanding of Digital Music Libraries and Archives.